Vietnam business profile - Deloitte Touche Tohmatsu International (Central, Hong Kong Deloitte Touche Tohmatsu International, 1993)
Contents: introduction to Vietnam; the economy; foreign investment; labor; foreign trade; accounting; taxation; finance and banking; business trip preparation.
Includes bibliography and index
Keywords: Quản trị kinh doanh